Implementation of the Forward Chaining Method in a Web-Based Human Skin Disease Diagnosis Expert System - Cahyo, Alqomari; Imamudiroyah, Mohammad Khoyyinudin; Cakra, Bisma Wahyu (Journal of Innovation and Computer Science, 2024)
Expert systems can be used as a tool to help diagnose early, including skin diseases, which often occur in tropical climates. Indonesia is one of the countries with a very high popularity of the spread of this skin disease. A technology-based media is needed to handle the problem of more public knowledge in diagnosing skin diseases early, quickly, and accurately. This study aims to implement forward chaining in an expert system for diagnosing skin diseases. The forward chaining method is used to carry out inference control. The Rapid Application Development (RAD) method is used as a methodology for developing an expert system, which consists of several stages, namely starting with the process of determining the objectives and scope of each aspect, making a prototype, collecting input from users, and testing and implementing the output produced. The results of this study are in the form of applications that the community can use to help diagnose early types of diseases and their treatments.